Amount of Cycloserine Emanating from Terizidone Metabolism and Relationship with Hepatic Function in Patients with Drug-Resistant Tuberculosis - Mwila Mulubwa; Pierre Mugabo (Adis, Springer Healthcare, 2019)
Abstract Background and objectives The dosing of cycloserine and terizidone is the same, as both drugs are considered equivalent or used interchangeably. Nevertheless, it is not certain from the literature that these drugs are interchangeable. Therefore, the amount of cycloserine resulting from the metabolism of terizidone and the relationship with hepatic function were determined. Methods This prospective clinical study involved 39 patients with drug-resistant tuberculosis admitted for an intensive phase of treatment. Cycloserine pharmacokinetic parameters for individual patients, like area under the curve (AUC), clearance (CLm/F), peak concentration (C max) and trough concentration (C min), were calculated from a previously validated joint population pharmacokinetic model of terizidone and cycloserine. Correlation and regression analyses were performed for pharmacokinetic parameters and unconjugated bilirubin (UB), conjugated bilirubin (CB), albumin, the ratio of aspartate transaminase to alanine aminotransferase (AST/ALT), or binding affinity of UB to albumin (K af), using R statistical software version 3.5.3. Results Thirty-eight patients took a daily dose of 750 mg terizidone, while one took 500 mg. The amount of cycloserine [median (range)] that emanated from terizidone metabolism was 51.6 (0.64-374) mg. C max (R 2 = 22%, p = 0.003) and C min (R 2 = 10.6%, p = 0.044) were significantly associated with increased CB concentration. C max was significantly associated with increased K af (R 2 = 10.1%, p = 0.048), while high CLm/F was significantly associated with decreased AST/ALT (R 2 = 21%, p = 0.003). Conclusions Cycloserine is not interchangeable with terizidone, as amounts are lower than expected. Cycloserine may be a predisposing factor to the development of hyperbilirubinaemia, as CLm/F is affected by hepatic function.